Prognosis associated with several different post-treatment reactions after hemoporfin mediated photodynamic therapy - Ping Diao; Lifeng Yang; Chenglong Han; Xian Jiang (Photodiagnosis and Photodynamic Therapy)
Hemoporfin mediated photodynamic therapy(HMME-PDT) has been proved safe and effective for treating PWS in both adults and children in previous articles, especially for lager segment lesions. However, crusts and scars associated with HMME-PDT cannot be ignored. The article briefly summarized several post-treatment reactions after HMME-PDT treatment relative to prognosis, and emphasized that early identification and intervention the post-treatment reactions after HMME-PDT, which has very important significance to prognosis.